Neuropsychological Performance: How Mental Health Drives Attentional Function in University-Level Football Athletes - Sacha Assadourian; Dima Daher; Catherine Leclerc; Antony Branco Lopes; Arnaud Saj (Sports)
This preliminary study investigates the potential relationship between electrophysiological profiles measured by quantitative electroencephalography (QEEG) and attentional performance in 34 university American football players. QEEG data revealed patterns associated with burnout, chronic pain, and insomnia among the athletes. Attentional performance was generally average, but players exhibited faster reaction times in the alertness task without warning, fewer errors in the sustained attention task, and lower scores in the divided attention task, favoring visual information over auditory information. Significant negative correlations emerged between QEEG profiles associated with burnout, ADHD, depression, and anxiety and specific attentional subcomponents. These findings suggest a link between mental health-related brain activity and attentional performance. In a clinical context, they emphasize the need for early detection and intervention in mental health problems. This might improve cognitive performance and well-being in athletes. However, due to the small sample size and the lack of a control group, these results are considered preliminary, and further research is required to confirm and expand on these associations.